Sociolingüistica de la elisión de la dental -/d/- en Madrid (Distrito de Salamanca) - Molina Martos, Isabel; Paredes García, Florentino (El Colegio de México, A.C., 2015)
This article analyzes the elision of intervocalic /d/ in Madrid (Salamanca district) and provides a social and linguistic description of the dual tendency of this change, conservative in the general context and innovative in the -ado context. Variationist analyses are contrasted and complemented with approaches that bring into the discussion individual contributions, in order to highlight the agentivity of speakers and the performative nature of language. We use statistic correlations and regression analyses to test the influence of 26 variables in the realization of the segment, and to measure the individual impact of the speakers in the innovation.  Original received: 2014/04/25Review sent to author: 2014/06/20Accepted: 2014/06/21